Knowledge Levels Regarding Ticks and Crimean-Congo Haemorrhagic Fever Among Veterinarians, Nurses and Nursing Students - Aydın, Mehmet Fatih; Dumanlı, Nazir (Van Yüzüncü Yıl Üniversitesi, 2017)
The aim of this study is to determine the knowledge levels regarding ticks and Crimean-Congo Hemorrhagic Fever among veterinarians, nurses and nursing students in Turkey. Survey was performed between July 2009 and April 2010 with a questionnaire consisting of 20 questions. Data were collected from 53 veterinarians, 62 nurses and 133 nursing students by face-to-face interviews. The people in the groups knew general characteristics of Crimean-Congo Hemorrhagic Fever, transmission of the disease and medical response with high percentage. Nursing students failed at the questions about general characteristics of ticks. Fourth-grade students were found more successful at 13 questions than other students, also nurses from Amasya were more successful at 16 questions than nurses from Bitlis. Veterinarians gave correct answers to 12 questions out of 20, nurses 6 out of 20 and students 1 out of 20 with the highest percentage and nurses and veterinarians answered one question with equal success. We have found that the participants of this survey have insufficient knowledge about some subjects for ticks and Crimean-Congo Hemorrhagic Fever. It is recommended that the health care workers should be informed about ticks and tick-borne diseases after graduation, also nursing students should receive education about vectors and vector-borne diseases.

Bu çalışmanın amacı Türkiye’deki veteriner, hemşire ve hemşirelik öğrencilerinin keneler ve Kırım-Kongo Kanamalı Ateşi yönünden bilgi seviyelerini belirlemektir. Araştırma Temmuz 2009 ve Nisan 2010 tarihleri ??arasında 20 sorudan oluşan bir anket ile yürütüldü. Veriler; 53 veteriner hekim, 62 hemşire ve 133 hemşirelik öğrencisinden yüz yüze görüşme yolu ile toplandı. Gruplardaki kişilerin Kırım-Kongo Kanamalı Ateşi’nin genel özellikleri, hastalığın bulaşması ve tıbbi müdahale konusunda yeterli oldukları görüldü. Hemşirelik öğrencilerinin kenelerin genel özellikleri hakkındaki sorularda başarısız oldukları, dördüncü sınıf öğrencilerinin 13 soruda diğer öğrencilerden, Amasya’daki hemşirelerin 16 soruda Bitlis’teki hemşirelerden daha başarılı oldukları saptandı. Veteriner Hekimlerin 20 sorudan 12’sine, hemşirelerin 6’sına ve öğrencilerin ise bir soruya en yüksek düzeyde doğru cevap verdikleri gözlemlenirken, 1 soruyu ise hemşire ile veteriner hekimlerin eşit sayıda doğru olarak cevapladıkları tespit edildi. Bu çalışmanın katılımcılarının keneler ve Kırım-Kongo Kanamalı Ateşi ile ilgili bazı konularda yetersiz bilgiye sahip oldukları görüldü. Sağlık çalışanlarının mezuniyet sonrasında keneler ve kenelerle bulaşan hastalıklar konusunda bilgilendirilmesi, ayrıca hemşirelik öğrencilerinin vektörler ve vektörlerle bulaşan hastalıklar konusunda eğitim alması gerektiği kanaatine varıldı.
Veteriner, Hemşire ve Hemşirelik Öğrencilerinin Keneler ve Kırım-Kongo Kanamalı Ateşi Yönünden Bilgi Seviyeleri